2007
DOI: 10.1124/mol.107.040980
|View full text |Cite
|
Sign up to set email alerts
|

Transport of Cisplatin by the Copper Efflux Transporter ATP7B

Abstract: ATP7B is a P-type ATPase that mediates the efflux of copper. Recent studies have demonstrated that ATP7B regulates the cellular efflux of cisplatin (DDP) and controls sensitivity to the cytotoxic effects of this drug. To determine whether DDP is a substrate for ATP7B, DDP transport was assayed in vesicles isolated from Sf9 cells infected with a baculovirus that expressed either the wild-type ATP7B or a mutant ATP7B that was unable to transport copper as a result of conversion of the transmembrane metal binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 33 publications
4
84
0
Order By: Relevance
“…The results obtained with 2008 cells confirmed earlier observations that increased expression of ATP7A (including cells that overexpress ATP7A after transfection) was associated with resistance to various other classes of chemotherapeutic agents (Owatari et al, 2007;Furukawa et al, 2008). Although, like ATP7B (Safaei et al, 2008), ATP7A may transport cDDP directly, it seems unlikely that ATP7A would transport all of the drugs for which resistance has been demonstrated; it is more likely that Sec61␤ controls other types of transporters or alters vesicle pH or that Sec61␤ or ATP7A alters the activity of the vesicle secretory pathway. These hypotheses remain to be tested.…”
Section: Discussionsupporting
confidence: 88%
“…The results obtained with 2008 cells confirmed earlier observations that increased expression of ATP7A (including cells that overexpress ATP7A after transfection) was associated with resistance to various other classes of chemotherapeutic agents (Owatari et al, 2007;Furukawa et al, 2008). Although, like ATP7B (Safaei et al, 2008), ATP7A may transport cDDP directly, it seems unlikely that ATP7A would transport all of the drugs for which resistance has been demonstrated; it is more likely that Sec61␤ controls other types of transporters or alters vesicle pH or that Sec61␤ or ATP7A alters the activity of the vesicle secretory pathway. These hypotheses remain to be tested.…”
Section: Discussionsupporting
confidence: 88%
“…There is now quite a large body of evidence, derived from multiple cell models, that CTR1 regulates the cytotoxicity of DDP by affecting drug uptake (Lin et al, 2002;Holzer et al, 2004aHolzer et al, ,b, 2006aHolzer and Howell, 2006;Larson et al, 2009;Jandial et al, 2009;Safaei et al, 2009) and that the copper exporters ATP7A (Samimi et al, , 2004aSamimi and Howell, 2006) and ATP7B (Katano et al, 2002(Katano et al, , 2003Safaei et al, 2004Safaei et al, , 2008Safaei, 2006) contribute to DDP resistance by enhancing efflux. The absence of CTR1 expression renders yeast and mammalian cells resistant to copper, DDP, carboplatin, and oxaliplatin (Lin et al, 2002;Holzer et al, 2004bHolzer et al, , 2006aLarson et al, 2009), whereas overexpression of CTR1 was found to sensitize cells to the toxic effects of these agents Noordhuis et al, 2008).…”
Section: Ctr1 Controls Uptake Of the Platinum-containing Drugsmentioning
confidence: 99%
“…We also lack quantitative measurements of copper transport. The indications are that the transport rates are low (12,13). It is assumed that when copper transport across membranes is assayed, it is the permeation step that is rate-limiting.…”
Section: Special Characteristics Of Copper Transportmentioning
confidence: 99%